CORRELATION BETWEEN THROMBOCYTOPENIA DEGREE AND PARASITE DENSITY IN CONFIRMED CASES OF Plasmodium falciparum AND Plasmodium vivax MALARIA - Nina Difla Muflikhah (Journal of Vocational Health Studies, 2025)
Background: Thrombocytopenia, a condition characterized by a low platelet count, is the most prevalent hematological abnormality observed in acute malaria patients. Malaria remains a major global public health problem, with more than 200 million clinical cases reported annually. Purpose: This study aimed to investigate the correlation between the degree of thrombocytopenia and the parasite density in confirmed cases of Plasmodium falciparum and Plasmodium vivax. Method: This research was a descriptive observational study using a cross-sectional design. Clinical hematological examinations and peripheral blood smear preparations were performed on malaria patients, followed by analysis of platelet count, hemoglobin levels, and leukocyte count. Result: Thrombocytopenia, commonly found in acute malaria, was observed in 63.4% of cases, underscoring its key role as a diagnostic biomarker. This study showed significant association between hemoglobin levels and thrombocytopenia severity (p-value < 0.05), whereas leukocyte counts did not show a significant association with thrombocytopenia severity (p-value > 0.05). The degree of thrombocytopenia differed between the two types of malaria, assisting the differentiation of infections. Anemia, another detailed hematological indicator, frequently found in P. falciparum cases. Conclusion: Understanding hematological indicator as key-role of malaria diagnosis is vital for accurate diagnosis and effective management of malaria, especially in endemic regions. Continued research and routine hematological surveillance are crucial to improving malaria control and treatment outcomes.